2013
DOI: 10.3390/biology2020755
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology of Cold-Active Proteases

Abstract: The bulk of Earth’s biosphere is cold (<5 °C) and inhabited by psychrophiles. Biocatalysts from psychrophilic organisms (psychrozymes) have attracted attention because of their application in the ongoing efforts to decrease energy consumption. Proteinases as a class represent the largest category of industrial enzymes. There has been an emphasis on employing cold-active proteases in detergents because this allows laundry operations at ambient temperatures. Proteases have been used in environmental bioremediati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 143 publications
2
42
0
Order By: Relevance
“…However, cold active enzymes obtained from cold adaptive microorganisms are active at lower temperature, therefore, energy saving and prevention of undesirable by-product formation could be possible [54,67]. Additionally, it has been reported that cold active proteolytic enzymes have higher specificity than mesophilic ones [54,67,68,69,70].…”
Section: Production Of Ace-inhibitory Peptides From Plantsmentioning
confidence: 99%
“…However, cold active enzymes obtained from cold adaptive microorganisms are active at lower temperature, therefore, energy saving and prevention of undesirable by-product formation could be possible [54,67]. Additionally, it has been reported that cold active proteolytic enzymes have higher specificity than mesophilic ones [54,67,68,69,70].…”
Section: Production Of Ace-inhibitory Peptides From Plantsmentioning
confidence: 99%
“…Enzymes are known to be sensitive to temperature changes and the change in activity of any particular enzyme to such conditions is a distinguishing characteristic of such an enzyme. The use of non-thermophilic, cold-adapted proteases in detergents is desired as it promotes decrease in energy consumption (Joshi and Satyanarayana, 2013). …”
Section: Effect Of Temperature On Protease Activitymentioning
confidence: 99%
“…They also find usage in research. They constitute one of the largest groups of industrial enzymes and account for up to 60% of the total global sale of enzymes (Joshi and Satyanarayana, 2013). Proteases can be sourced from animals, plants, viruses, bacteria and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the phytases have been reported to possess even number of cysteine residues which might be involved in the formation of disulphide bridges as in Aspergillus niger [27]. The enzyme is insensitive to phenylmethanesulphoonyl fluoride (PMSF), a well-known serine protease inhibitor [28]. N-ethylmaleimide (NEM) had no observable effect on the enzyme activity.…”
Section: Effect Of Various Modulators On Rpphy Activitymentioning
confidence: 99%